Factors affecting gender diversity in Malaysia - Abdullah, Shamsul Nahar (2013)
The representation of women at the decision-making level in Malaysia has received special attention from the government since 2004, the year in which it adopted a policy requiring that 30 per cent of the posts at decision-making level in the public sector be filled by women. The objective of this paper is to examine the factors that determine the appointment of women to the boards of Malaysian large firms. Large firms were chosen in this study because they have the resources and the capacity to adopt the policy more readily compared to smaller firms. The results reveal that gender diversity is positively associated with board size and the presence of family on the board. That is, the larger the board is, the more likely it is that women sit on it. The fact that the presence of women on the board is associated with the presence of one or more family members on the board means that the appointment of women to the board is very much influenced by family ties rather than commercial reasons. The results show that firm performance is negatively associated with gender diversity. That is, firms with low financial performance are more likely to have women on their boards. Hence, taken altogether, the evidence suggests that the appointment of women to the board is very much driven by tokenism and family connection rather than by the business case.